"I'm not what I used to be": A qualitative study exploring how young people experience being diagnosed with a chronic illness. (27th January 2019) - Kirk, Susan; Hinton, Denise
Abstract: Background: Childhood long‐term conditions are usually diagnosed in infancy or early childhood. Little is known about the particular experiences and needs of young people who receive a chronic illness diagnosis during adolescence or late childhood. This paper will examine this experience in relation to multiple sclerosis (MS), which is increasingly being diagnosed before adulthood. Aims: To explore how young people experience an MS diagnosis. Methods: Qualitative study using a grounded theory approach. In‐depth interviews were conducted with 21 young people diagnosed with MS. Participants were recruited through health service and voluntary sector organizations in the United Kingdom. Results: Young people's pre‐illness normality was disrupted by the diagnosis of a chronic illness (MS). Participants experienced their body as changed physically, cognitively, and emotionally and as changeable due to symptom unpredictability. This influenced how participants perceived and presented their identity, disrupted their relationships, and altered their future biography. Young people developed strategies to manage their condition and identities in order to incorporate MS into their current and future lives, which required continual illness and identity work in response to changing symptoms, social contexts, and relationships. Conclusions: Although young peoples' experience of living with chronic illness has been widely explored, the aftermath of diagnosis has been underresearched from their perspective. This study contributes to this knowledge gap by illuminating how young people experience a chronic illness diagnosis and negotiate the resulting changes to their identity, relationships, and future. The findings suggest that young people need preparation and support in disclosing their diagnosis to others. Professionals supporting young people with long‐term conditions need to work closely with specialist mental health services to ensure that they receive appropriate emotional support. Schools have an important role in ensuring young people with long‐term conditions achieve their academic potential and receive appropriate careers advice.